Experimental results of the optimized management of an EMS-equipped small-size prosumer. (August 2018) - Magnani, Sandro; Danti, Piero; Cauchi, Giovanni
Abstract: The increasing penetration of the Distributed Generation in the power network has, globally, led to sensitive benefits in terms of reduction of the energy environmental footprint and, locally, in the reduction of the electric and thermal supply costs. In the Italian context the common paradigm consists in the installation of renewable and/or fossil sources to supply part of the loads requirements, with simple management logics of the local generators. The effectiveness of these solutions can be furtherly increased by optimizing the operations of the local system as a whole: the study presents the experimental performance of the plant management by a smart EMS prototype installed in a small industrial context, for a time space of more than one year. The test site is equipped with both renewable sources, i.e. a PV plant and a small wind turbine, and a natural gas µ-CCHP unit, these latter coupled with thermal storage tanks; additional flexibility is provided by the Real Time Pricing contract with the power distribution operator, giving to the plant management further complication. After a detailed description of the developed EMS and of the plant layout, the results will be presented from both a technical/economic and an environmental point of view, focusing on the relevant aspects and paying particular attention on the most critical points.